Reasons of using complementary and alternative medicines (CAM) among elderly Malaysians of Kuala Lumpur and Selangor states: an exploratory study - Mitha, Shahid; Nagarajan , Vimalan; Babar, Muneer Gohar; Siddiqui, Mohammad Jamshed Ahmad; Jamshed, Shazia Qasim (Elsevier, 2013)
Background: This study is aimed to explore the types of CAM and reasons of using CAM among elderly Malaysians. Method: This cross-sectional study was conducted on a sample of 256 conveniently selected elderly Malaysians who were residing in the states of Selangor and Kuala Lumpur. A pre-validated interviewadministered questionnaire was used to gather information. Data was entered into PASW version 18 and analyzed. Results: A total of 256 questionnaires were included in the study. A response rate of 64% was achieved. Out of 256 respondents, 92 (35.9%) were male while 164 (64.1%) were female. More than half of the respondents (n ¼ 141; 55.1%) agreed that CAM is more effective than allopathic medicine. Chinese respondents showed strong belief in the effectiveness of CAM. In terms of safety of CAM, close to three quarters of respondents (n ¼ 178; 69.5%) believed that CAM is safer than allopathic medicine. A large majority of respondents agreed that CAM has less side effects compared to allopathic medicine (n ¼ 201; 78.5%) and also agreed that CAM is good to maintain overall health and wellbeing (n ¼ 212; 82.8%). A majority of the respondents expressed that they use CAM because allopathic medicine is less effective (n ¼ 113; 44.1%). Conclusion: The current study reflects the reasons of using CAM among lay public from different ethnicities. There are no reports of adverse effects related to CAM use. Future approaches should be intended for awareness campaigns for consumers, highlighting safety profile of CAM and as well as forbidding their use without the consultation of healthcare professional.